Development of Real-Time Immuno-PCR Based on Phage Displayed an Anti-Idiotypic Nanobody for Quantitative Determination of Citrinin in Monascus - Wenping Huang; Zhui Tu; Zhenqiang Ning; Qinghua He; Yanping Li (Toxins, 2019)
Citrinin (CIT) is a mycotoxin that has been detected in agricultural products, feedstuff, and Monascus products. At present, research has been performed to develop methods for CIT detection, mainly through TLC, HPLC, biosensor, and immunoassay. The immunoassay method is popular with researchers because of its speed, economy, simplicity, and ease of control. However, mycotoxins are inevitably introduced during the determination. Immunoassays require the use of toxins coupled to carrier proteins or enzymes to make competitive antigens. In this study, anti-idiotypic nanobody X27 as CIT mimetic antigen was used as non-toxic surrogate reagents in immunoassay. Therefore, the X27-based real-time immuno-PCR (rtIPCR) method had been established after optimal experiments of annealing temperature and amplification efficiency of real-time PCR, concentration of coating antibody, phage X27, and methyl alcohol. The IC50 value of the established method in the present study is 9.86 ± 2.52 ng/mL, which is nearly equivalent to the traditional phage ELISA method. However, the linear range is of 0.1−1000 ng/mL, which has been broadened 10-fold compared to the phage ELISA method. Besides, the X27-based rtIPCR method has no cross-reactivity to the common mycotoxins, like aflatoxin B1 (AFB1), deoxynivalenol (DON), ochratoxin A (OTA), and zearalenone (ZEN). The method has also been applied to the determination of CIT in rice flour and flour samples, and the recovery was found to be in the range of 90.0−104.6% and 75.8−110.0% respectively. There was no significant difference in the results between the rtIPCR and UPLC−MS. The anti-idiotypic nanobody as a non-toxic surrogate of CIT makes rtIPCR a promising method for actual CIT analysis in Monascus products.